The Influence of Population Growth on the Development of Padang Panjang City Settlements in 2000-2020 - Nur janahti; Paus Iskarni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research was conducted in Padang Panjang City with the aim to determine: 1) Population Growth of Padang Panjang City from 2000 to 2020, 2) Development of the Settlement Area of Padang Panjang City from 2000 to 2020, 3) The Influence of Population Growth on the Development of Settlements in Padang Panjang City from 2000 to 2020. The research method employed was descriptive research with a quantitative approach. The results of this study indicate that 1) The population growth rate of Padang Panjang City from 2000-2020 is 3.44%, 2) The development of the settlement area in Padang Panjang City from 2000 to 2020 is 28.28 hectares, 3) Population growth has an influence of 25,9% on the development of settlements, while the remaining 74,1% is explained by other factors not examined. Specifically, each increase of one person in the population contributes to an increase in the settlement area by approximately 0.692 hectares.